2015
DOI: 10.1007/s10571-015-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Depletion Does not Modify the Short-Term Brain Hypometabolism and Hippocampal Neurodegeneration Induced by the Lithium–Pilocarpine Model of Status Epilepticus in Rats

Abstract: It has been reported that fluoxetine, a selective serotonin (5-hydroxytryptamine; 5-HT) reuptake inhibitor, has neuroprotective properties in the lithium-pilocarpine model of status epilepticus (SE) in rats. The aim of the present study was to investigate the effect of 5-HT depletion by short-term administration of p-chlorophenylalanine (PCPA), a specific tryptophan hydroxylase inhibitor, on the brain hypometabolism and neurodegeneration induced in the acute phase of this SE model. Our results show that 5-HT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…PCPA (Sigma, St. Louis, MO, USA), a specific inhibitor of serotonin (5-HT) biosynthesis, was administered (100 mg/kg) once a day for seven days, as described previously [35]. PCPA has shown a high degree of 5-HT depletion (>90%) yielded by similar treatment [36].…”
Section: Experimental Designmentioning
confidence: 99%
“…PCPA (Sigma, St. Louis, MO, USA), a specific inhibitor of serotonin (5-HT) biosynthesis, was administered (100 mg/kg) once a day for seven days, as described previously [35]. PCPA has shown a high degree of 5-HT depletion (>90%) yielded by similar treatment [36].…”
Section: Experimental Designmentioning
confidence: 99%
“…Shiha and colleagues showed that subacute treatment with fluoxetine, a selective serotonin reuptake inhibitor, prevented short-term hypometabolism following pilocarpine-induced SE in rats (Shiha et al, 2015). Similar approach was used to evaluate the efficacy of p-chlorophenylalanine, a specific tryptophan hydroxylase inhibitor, without any effect (Garcia-Garcia et al, 2016). On the contrary, treatment with metyrapone, an 11-hydroxylase inhibitor, prevented hypometabolism and brain damage caused by SE in rats (Garcia-Garcia et al, 2017).…”
Section: Imaging Brain Activationmentioning
confidence: 99%
“…La espectroscopia de resonancia magnética (MRS, acrónimo inglés de Magnetic Resonance Spectroscopy) detecta metabolitos cerebrales asociados con el SE como el N-acetil aspartato (NAA), los neurotransmisores GABA y glutamato, metabolitos como el lactato y biomarcadores de glía como el mio-inositol (mIns), cuyos niveles aumentan en fases iniciales de la epileptogénesis en varios modelos animales de SE (15). Los estudios de PET con 2-desoxi-2-( 18 F) fluoro-D-glucosa ( 18 F-FDG) en diferentes modelos animales de ELT detectan hipermetabolismo cerebral tras las crisis epilépticas agudas (16,17). Además, en el periodo silente es característico el hipometabolismo cerebral que es predictivo de la generación de crisis epilépticas en modelos de kindling químico (18).…”
Section: Descargas Intercríticasunclassified